2002
DOI: 10.1002/mpo.10076
|View full text |Cite
|
Sign up to set email alerts
|

Platinum agents in the treatment of osteosarcoma: Efficacy of cisplatin vs. carboplatin in human osteosarcoma cell lines

Abstract: Our findings suggest that CBDCA at a two- to four-fold higher concentration than cDDP has potential therapeutic activity in platinum sensitive osteosarcomas, particularly when cDDP cytotoxicity compromises therapeutic efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…CBDCA is a synthesized platinum compound with fewer side effects as compared to those of cisplatin. Preclinical data of CBDCA against osteosarcoma was rather indicative (Bergman et al, 1996;Crnalic et al, 1996;Robson et al, 2002) of its ability to induce regression of osteosarcoma. The efficacy of CBDCA was comparable to cisplatin in treatment of several solid tumors, especially in adults (Lokich and Anderson, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…CBDCA is a synthesized platinum compound with fewer side effects as compared to those of cisplatin. Preclinical data of CBDCA against osteosarcoma was rather indicative (Bergman et al, 1996;Crnalic et al, 1996;Robson et al, 2002) of its ability to induce regression of osteosarcoma. The efficacy of CBDCA was comparable to cisplatin in treatment of several solid tumors, especially in adults (Lokich and Anderson, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The variable response of osteosarcoma cell lines to conventional chemotherapeutical agents has been described before in several reports. Robson et al 24 showed that cisplatin has no cytotoxic effect on U-2 osteosarcoma cells at a concentration of 20 mM, while HOS and MG-63 cells showed an ED 50 at 9.0 and 12.2 mM, respectively. Gomes et al 25 showed that doxorubicin was able to significantly induce cell death in SAOS-2 cells, but no effect was observed for HOS and U-2 OS cells.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have suggested that the complexes have a square planar structure and are much more inert [29] or that the loss of methanol from the ligands causes esterification of the carboxyl groups present in the fungal cell walls [30]. The inhibition values obtained from the Pt(II) complexes could arise from deeper effects on the DNA replication and transcription machinery of the cell since they are known to bind to the internal groove of the DNA helix and interfering with normal function of arresting DNA polymerase [31,32]. This effect usually acts as a trigger leading to apoptosis.…”
Section: Antifungal Activity Of N-benzoyl-n-alkylthioureides and N-bementioning
confidence: 99%
“…The compounds were tested in the presence of 500 ppm of ligands 29, and 30 and their Ni(II) complexes (31) and (32). Ni(II) complexes (31) and (32) have been characterized by X-ray crystallography by del Campo et al in 2002 [18]. In general, inhibition by the ligands was higher than that of the complexes, while the N,N-diethyl substituents had a greater influence on the antifungal activity than the N-morpholino substituent (see Schemes 3 and 4).…”
Section: Antifungal Activity Of N-benzoyl-nnmentioning
confidence: 99%
See 1 more Smart Citation